2010
DOI: 10.2147/dhps.s7634
|View full text |Cite
|
Sign up to set email alerts
|

Antidepressant-associated sexual dysfunction: impact, effects, and treatment

Abstract: Sexual dysfunction is a common side effect of antidepressants and can have significant impact on the person’s quality of life, relationships, mental health, and recovery. The reported incidence of sexual dysfunction associated with antidepressant medication varies considerably between studies, making it difficult to estimate the exact incidence or prevalence. The sexual problems reported range from decreased sexual desire, decreased sexual excitement, diminished or delayed orgasm, to erection or delayed ejacul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
100
1
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 166 publications
(106 citation statements)
references
References 56 publications
3
100
1
2
Order By: Relevance
“…Major depression is often associated with sexual dysfunctions [2,3]. Treatment of the depression with antidepressants complicates the situation considerably.…”
mentioning
confidence: 99%
“…Major depression is often associated with sexual dysfunctions [2,3]. Treatment of the depression with antidepressants complicates the situation considerably.…”
mentioning
confidence: 99%
“…Studies have found that increased central serotonergic activity is involved in causing sexual dysfunction. [5] Studies have shown that amitriptyline use in migraine is associated with adverse effects like weight gain, constipation, blurring of vision, dryness of mouth, etc. But it is rarely reported that its use is associated with sexual dysfunction as an adverse effect in the treatment of migraine.…”
Section: Discussionmentioning
confidence: 99%
“…It can have significant impact on the person's quality of life, quality of relationships and selfesteem. [5] Hence a regular monitoring of adverse reactions in patients who are on long term drugs is needed. Since most of these adverse effects are reversible, it is important…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations